Pengaruh Salesmanship dan Sales Promotion Terhadap Penjualan Mobil Toyota pada PT. Astra International, Tbk (Toyota Auto2000 Karawang) - Fitri Handayani; Dene Herwanto; Wahyudin Wahyudin (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Companies need goals and vision to function. To achieve its goals, such as maximizing profits, the company must sell products. PT Astra International, Tbk – Auto2000 Karawang Branch is an authorized Toyota dealer in Indonesia that sells cars, spare parts and accessories. They also provide services such as Service and Body Pain. Auto2000 Karawang Branch and PT. Astra International are both car dealers that sell cars on a large, medium or small scale. Their competitive business models add to the splendor of competition in the business world. Because businesses must compete in changing cultural, technological, economic and social conditions, each company uses a different marketing strategy. This study looks at Toyota brand cars to see if Salesmanship and Sales Promotion affect their sales. This data analysis shows that Sales Promotion and Salesmanship increased PT Astra International's sales. This is achieved through the use of SPSS, which processes data in a quantitative manner.